A comparative analysis of the South African and Australian general tax avoidance enactments - Aucamp, Johan Louis (Centre for Law and Society, 2026)
From a tax planning perspective, it is important to take note of the general trend of the developments in anti-tax avoidance provisions and the manner in which they are interpreted by the Supreme Court. From an international perspective it is important to take cognizance of the fact that internationally, a flurry of tax avoidance provisions are being promulgated to curtail the increasing efforts of taxpayers to avoid the effect of harsh tax measures being taken by different authorities.